Treatment Modalities, Analgesic Use, Cancer Stage, and Cancer Location on Symptom Clusters in Head and Neck Cancer Patients - wyssie ika sari (Professional Health Journal)
Introduction: Head and neck cancer patients generally have the same symptoms, but the prevalence and severity can vary. The prevalence and severity of symptoms in a cluster are related to the overall symptom experience. The prevalence and severity of symptoms in a cluster can be related to the patient's health and illness state. Objectives: This research aims to determine the relationship between treatment modalities, analgesic use, cancer stage, and cancer location on symptom clusters in head and neck cancer patients. Methods: The method used is analytical observational with a cross-sectional approach. The sample inclusion criteria were as follows: head and neck cancer without metastatic disease to the brain, cooperative and good at communicating, and age 18-70 years. Meanwhile, the exclusion criteria are not completing the questionnaire due to critical condition, mental disorders, death, and patient going home. The sampling technique used was consecutive sampling, consisting of 111 patients at Dr. Kariadi Central General Hospital of Semarang. Data analysis using Spearman Rho. Results: The relationship between the significance values ​​of the treatment modality variables for sickness and gastrointestinal symptom clusters, the use of analgesics for gastrointestinal symptom clusters, the location of cancer for emotional symptom clusters, and the stage with symptom clusters is <0.05. The research results also show that several variables also have a significance value of > 0.05. Conclusions: Good identification of treatment modalities, use of analgesics, cancer stage, and cancer location is expected to be able to overcome symptom clusters in head and neck cancer.